From the Classroom to the Dark Room: Corruption Resistance in the World of Education - Mutia Oktavianti; Na’imah; Siska Dewi; Adinda (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Corruption in Indonesian education is still a serious problem that threatens the integrity and quality of educational institutions. This study aims to analyze the forms of resistance to corruption that emerge in the educational environment and to formulate effective strategies in strengthening anti-corruption culture. Using a qualitative approach based on literature studies, this study examines literature, official reports, and national survey data related to corruption practices and resistance in the education sector. The results of the study indicate that resistance to corruption has begun to grow significantly, both at the institutional and personal levels. Forms of resistance include the integration of anti-corruption education into the curriculum, the habituation of a clean culture in schools and campuses, and the active participation of teachers, students, students, and the community in monitoring and reporting violations. Data from the 2024 KPK Education Integrity Assessment Survey (SPI) shows an increase in awareness and participation of education actors, although the application of anti-corruption values is not yet evenly distributed and consistent. This study emphasizes the importance of synergy between educational character, transparent governance, and the use of information technology as a strategy for corruption resistance. This study recommends strengthening anti-corruption literacy and sector collaboration to create a clean, transparent, and integrated educational environment.